A Stretchable Multicolor Display and Touch Interface Using Photopatterning and Transfer Printing. Issue 44 (22nd September 2016) - Li, Shuo; Peele, Bryan N.; Larson, Chris M.; Zhao, Huichan; Shepherd, Robert F.
Abstract : An intrinsically soft and stretchable multicolor display and touch interface is reported. Red, green, and blue pixels are formed separately by photopatterning transition‐metal‐doped ZnS embedded in silicone gels and transfer printing onto an elastomeric dielectric sheet. The device shows stable illumination while being stretched up to 200% area strain or under different deformation modalities. It also introduces capabilities for dynamic colorations and multipoint capacitive touch sensing.